2012
DOI: 10.5125/jkaoms.2012.38.3.134
|View full text |Cite
|
Sign up to set email alerts
|

Bone graft material using teeth

Abstract: (J Korean Assoc Oral Maxillofac Surg 2012;38:134-8) Autogenous tooth bone graft material contains organic and inorganic components for osteoinductive and osteoconductive healing. The clinical availability and safety of this material have been confirmed by various experimental and clinical studies. In the future, allogenic and xenogenic tooth bone graft materials, ideal scaffold using teeth for stem cells and bone growth factors, and endodontic and tooth restorative material will be developed.Key words: Toot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…The major drawbacks of autogenous bone are that it requires a secondary donor site and can be collected in a rather limited amount. Allogenic bone graft, which was developed as an alternative material for autogenic bone graft, has osteoinductive ability, but facesthe risk of viral infections, while heterogenic bone and synthetic bones have only osteoconductive ability; therefore, these grafts are limited in their ability to promote the regeneration of new bone [1]. The teeth are known to be an organic-inorganic hybrid composed of calcium phosphates with collagen and other organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The major drawbacks of autogenous bone are that it requires a secondary donor site and can be collected in a rather limited amount. Allogenic bone graft, which was developed as an alternative material for autogenic bone graft, has osteoinductive ability, but facesthe risk of viral infections, while heterogenic bone and synthetic bones have only osteoconductive ability; therefore, these grafts are limited in their ability to promote the regeneration of new bone [1]. The teeth are known to be an organic-inorganic hybrid composed of calcium phosphates with collagen and other organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Apatite in bone tissue has low crystallinity with nanometer‐scale particle sizes. By an increase in its crystallinity and size of particles, its biodegradation in the human body will become impossible and its osteoconductivity will decrease . This issue must be taken into account in simulation of natural denaturated scaffolds containing hydroxyapatite.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of dentin in regeneration of tooth and bone has attracted the attention of researchers in the recent years . Due to the high similarity of dentin and bone in terms of their chemical composition (35% organics and 65% minerals), researchers have considered dentin as an alternative for use in bone regeneration . In this regard, a question arises that whether dentin requires any processing prior to use in tissue engineering and that what techniques have been used for dentin processing so far.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, an autogenous bone graft material was developed from extracted teeth, and subjected to many basic and clinical studies. It has since been found to be an excellent biocompatible material with osteoinductive and osteoconductive potential [5][6][7][8]15,16) . Researches that demineralized dentin matrix (DDM) can play a role as the scaffold of bone morphogenic protein (BMP) and growth factors were announced.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical effectiveness of autogenous tooth bone graft, which was domestically developed in 2008 and now being actively used, was already proved. Also, it was reported that it showed the similar healing state to free autogenous bone graft as its osteoconductive and osteoinductive healing were excellent and bone remodeling was good [5][6][7] . Meanwhile, although tissue engineering research using various growth factors, bone morphogenic protein, and stem cell, etc is actively being performed worldwide, the appropriate scaffold to carry them have not been developed much.…”
Section: Introductionmentioning
confidence: 95%